Half Hour Hara and the Case of the Broken Eggs - Anidi, Ugo; Adeshida, Folasade (Nigeria, 2022)
Hara can't help getting into trouble, no matter how hard she tries. Sometimes, all she wants to do is look at something but somehow, it breaks! Like Daddy's special TV and Mummy's fancy plates. Now, the eggs for making Mummy's birthday cake are smashed and splattered on the floor! Hara didn't break them, but she knows no one will believe her. She has to find the real culprit before Daddy get back home in 30minutes - or she will be in trouble again!...
Keywords: Adventure; Juvenile Fiction